Effect of airflow rate and honeycomb channels addition on the efficiency of bagasse-fuelled top-lit updraft (TLUD) gasification stove - Clarissa Putri Sholeha; Muhammad Trifiananto; Mahros Darsin; Andi Sanata; Imam Sholahuddin; Ariyo Anindito (University of Muhammadiyah Malang, 2024)
The use of Liquefied Petroleum Gas (LPG) fuels has increased over time and has triggered the innovation of renewable fuels that do not affect the environment. This renewable fuel is biomass. Biomass is derived from organic materials of plants or animals that can be used as fuel. The conversion of biomass into thermal energy using gasification stoves can increase thermal efficiency up to twice that of conventional biomass combustion. Common stoves that use nowadays is Top-Lit Updraft (TLUD) gasifier that easy to optimize. This type of gasifier has a simple design and can be fuelled with any type of biomass with a water composition of less than 20%. Gasification stoves have so far been developed using various biomass fuels, one of which is bagasse waste. Bagasse is also easy to obtain in Indonesia because it has an abundant number of quantities. In addition to the fuel aspect, the ability of the gasification stove to produce good thermal efficiency depends on the stove design, such as stove type, stove dimensions, and combustion airflow rate. It is tested with the water boiling test method using variations of airflow rate of 2 m/s, 3.5 m/s, 5 m/s, and 6.5 m/s and honeycomb channels addition. As a result, it reached 30% thermal efficiency.